Verzameling Marguerite Arp-Hagenbach. (Otterlo : Rijksmuseum Kröller-Müller, 1970)
Agam, Yaakov ; Albers, Josef ; Arp, Jean ; Bill, Max ; Delaunay, Robert ; Delaunay, Sonia ; Duchamp, Marcel ; Eggeling, Viking ; Freundlich, Otto ; Giacometti, Alberto ; Gielzes, Albert ; Gonzales, Julio ; etc.
Verzameling Marguerite Arp-Hagenbach, Rijksmuseum Kröller-Müller, Otterlo, 28 Juni - 16 Augustus 1970
boek